POLYSACCHARIDE PST001 ISOLATED FROM THE SEED KERNEL OF TAMARINDUS INDICA INDUCES APOPTOSIS IN MURINE CANCER CELLS : Life Science-Pharmaceutics - S.R ARAVIND; M JOSEPH, MANU; VARGHESE, SHEEJA; BALARAM, PRABHA; T.T. SREELEKHA (International Journal of Life Science and Pharma Research, 2012)
The chemotherapeutic agents long used in oncologic treatment produce deleterious side effects. Polysaccharides isolated from plants and mushrooms were widely studied to find an additional agent for cancer therapy. Present study evaluated the in vitro anti-tumor effect of a polysaccharide from seed kernel of Tamarindus indica (PST001) on murine cancer cells DLA and EAC. PST001 has antitumor activity and could inhibit the cell proliferation significantly. DLA cells showed an IC50 value of 91.14 µg/ml for PST001 after 48 hours of treatment, whereas EAC cells showed no IC50 value but an inhibition of 46.45% was observed. DLA and EAC cells treated with PST001 showed typical apoptotic morphology when stained with Acridine Orange/ Ethidium bromide. The results of flow cytometry analysis for Caspase-3 activation and Annexin- V staining showed that PST001 could induce apoptosis. Cell cycle analysis also supports apoptosis, where as distribution of cells in the different cell cycle phases are normal in EAC cells and a slight change in DLA cells. DNA isolated from DLA cells treated with 100 µg/ml PST001 showed DNA ladder specific for apoptosis on agarose gel elctrophoresis. The above results suggest that PST001 could suppress DLA and EAC cell growth and reduce the cell survival by inducing apoptosis of tumor cells.